La ergonomía y su incidencia en el rendimiento laboral en los colaboradores de la Cooperativa de Ahorro y Crédito Vilcabamba-CACVIL - Gaona Jiménez, María Alejandra (2024)
When talking about ergonomics, it is often thought that it is essential only for rest, however, addressing it in the workplace is nowadays considered an indispensable factor to ensure the comfort, efficiency and safety of workers. The main objective of this research was to establish the ergonomic risk factors that affect the work performance of the collaborators of the Cooperativa de Ahorro y Crédito Vilcabamba- CACVIL, and two specific objectives were also determined, the first aimed at identifying the risk factors to which the internal actors of the company are exposed and the second to analyze their work performance. This research has a qualitative approach, of a descriptive exploratory type, with a non-experimental research design; to collect information, the following methods were used: a questionnaire and the ergonomic evaluation method for office work (ROSA) applied to the 12 collaborators and an Ergonomic Checklist (ECL) for the manager of the company. The results showed that there are physical risks due to work posture and unergonomic workplaces, cognitive risks due to mental workload and lack of active breaks, environmental risks due to inadequate temperature, and also that the work performance of the employees is favorable for the company. Finally, an improvement plan was proposed, which proposes compliance with certain articles of the Labor Code, the Andean Instrument for Safety and Health at Work and the Safety and Health Regulations for workers in Ecuador, so that the cooperative can put them into practice and thus improve the quality of life in the company and increase productivity and job satisfaction.